The fabJ-encoded beta-ketoacyl-[acyl carrier protein] synthase IV from Escherichia coli is sensitive to cerulenin and specific for short-chain substrates. - Siggaard-Andersen, M (1994)
A fourth fatty acid condensing enzyme was isolated from Escherichia coli by its ability to restore elongating activity to a protein extract which had been treated with cerulenin, a condensing enzyme-specific inhibitor. The purified beta-ketoacyl-[acyl carrier protein] (ACP) synthase IV [3-oxoacyl-ACP synthase; acyl-ACP:malonyl-ACP C-acyltransferase (decarboxylating), EC 2.3.1.41] (KAS IV) is specific for short-chain acyl-ACP substrates. The enzyme is stable at 43 degrees C and very sensitive to cerulenin (50% inhibition at 3 microM), which binds covalently. A condensing enzyme-specific antibody raised to an expressed open reading frame from barley was used to identify KAS IV protein in Western blots, and the sequence obtained for 30 amino-terminal residues. This led to the isolation of the fabJ gene located in the fab cluster at 24.8 min of the E. coli chromosome. The fabJ gene encodes a polypeptide of 413 amino acids and molecular mass 43 kDa that shows 38% identity and 64% similarity to the fabB-encoded KAS I. The amino acid sequence of KAS IV, however, is more similar to all other published condensing enzyme sequences than the KAS I sequence is. A specialized putative function for this enzyme is to supply the octanoic substrates for lipoic acid biosynthesis. We predict that an analogue of KAS IV with the same function will be found in plant mitochondria. The described complementation assay can be used to detect condensing enzymes with other substrate specificities by supplementing the cerulenin-treated extract with appropriate purified KAS enzymes.